Clinical Use of a Real-World Low Carbohydrate Diet Resulting in Reduction of Insulin Dose, Hemoglobin A1c, and Weight - Wolver, Susan; Fadel, Kristen; Fieger, Ethan; Aburish, Zein; O'Rourke, Brennen; Chandler, Toni-Marie; Shimotani, Dorian; Clingempeel, Natasha; Jain, Shuchi; Jain, Aashish; Puri, Puneet (Frontiers in Nutrition, 2021)
INTRODUCTION Type 2 Diabetes Mellitus (T2DM) is increasing in epidemic proportions. In addition to the morbidity and mortality, for those treated with insulin, the physical, psychological, and financial tolls are often greater. Our real-world study evaluated a Low Carbohydrate Diet (LCD) in patients with T2DM on insulin with respect to glycemic control, insulin reduction, and weight loss. MATERIALS AND METHODS A prospective cohort study was conducted via an Electronic Medical Record search for patients attending the Virginia Commonwealth University Medical Weight Loss Program from 2014-2020 with Type 2 Diabetes Mellitus who initially presented on insulin. Data was extracted for one year after enrollment. The weight loss program focuses on a LCD. RESULTS Of 185 participants, the mean (±SD) age was 56.1 (9.9) years. 70% were female and 63% were black. 85 completed 12 months (45.9%), reduced their median (25-75% interquartile range, IQR) insulin dose from 69 to 0 units (0-18, p<0.0001), HbA1c from 8% to 6.9% (6.2-7.8, p<0.0001), and weight from 116 kg to 99 kg (85-120, p<001). 86% who completed 12 months were able to reduce or discontinue insulin, with 70.6% completely discontinuing. Among all participants who completed 3, 6, or 12 months, 97.6% were able to reduce or eliminate insulin use. CONCLUSION In patients with T2DM on a LCD, it is possible to reduce and even discontinue insulin use while facilitating weight loss and achieving glycemic control. A Low Carbohydrate Diet should be offered to all patients with diabetes, especially those using insulin.